When Colombia met Senegal: A photostory - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In September 2013, ten agricultural stakeholders from Colombia traveled to Kaffrine, Senegal for a weeklong south-south learning exchange. Delegates from Colombia included officials from the rice and cereals sector (FEDEARROZ and FENALCE), the national meteorological institute (IDEAM), and the National University of Colombia. The exchange was supported by the International Center for Tropical Agriculture and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). Kaffrine, Senegal is a focal CCAFS research site and global leader in topics such as climate information services and seasonal forecasting.